Would the Real Loneliness Please Stand Up? The Validity of Loneliness Scores and the Reliability of Single-Item Scores. (June 2023) - Mund, Marcus; Maes, Marlies; Drewke, Pia M.; Gutzeit, Antonia; Jaki, Isabel; Qualter, Pamela
Several measures that assess loneliness have been developed for adults. Across three studies, we investigated psychometric features of scores of different versions of the Rasch-Type Loneliness Scale, the University of California Los Angeles Loneliness Scale, and three single-item measures. In Study 1 ( N = 697 self-ratings, N = 282 informant-ratings of 160 targets) and Study 2 ( N = 1, 216 individuals from 608 couples), we investigated convergent validity, self-informant agreement, and nomological nets of the item scores using correlates related to demographic aspects, personality, satisfaction, and network characteristics. In Study 3 ( N = 411), we estimated a reliability ofr x x > . 70 for scores of three single-item measures of loneliness. Overall, scores of all measures and their nomological nets were highly correlated within and across studies, indicating that the scores of the included measures are all reliable and valid. Recommendations for choosing a loneliness measure are discussed.